Miniaturization of Broadband Wilkinson Power Dividers - Nadera Najib; Kok Yeow You; Chia Yew Lee; Mohamad Ngasri Dimon; Nor Hisham Khamis (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper proposed three modified Wilkinson power dividers in order to achieve a size reduction and a wide bandwidth. The first structure presented the power divider using compact folded step impedance transmission lines rather than the uniform microstrip line design for operating center frequency of 3 GHz. The second structure showed the power divider with delta-stub for 2.4 GHz. Finally, the third modified structure introduced the two-section Wilkinson power divider using series-delta stub for center frequency of 2.4 GHz as well. The study managed to get an overall dimension of 15 mm × 9.5 mm for the first proposed design achieving a reduction of 75.6 % and fractional bandwidth of 133 %. For the second proposed structure, the size was 15 mm × 15 mm with a reduction of 56 % and fractional bandwidth of 56 %.  While the third design size was 17 mm × 15 mm with a reduction of 63.6 % and the structure achieved a broadband bandwidth with fractional bandwidth of 220 %.  The proposed power dividers used RT/duroid 5880 substrate with a thickness of 0.38 mm. Simulation and measurement results indicated that the modified power dividers showed equal power division, good phase balance, high isolation between output ports, and good return loss better than -12 dB covering the operating frequency range.